1966
DOI: 10.1136/jnnp.29.6.545
|View full text |Cite
|
Sign up to set email alerts
|

Transection of the pituitary stalk in man: anatomical changes in the pituitary glands of 21 patients

Abstract: In recent years hypophysectomy (Luft and Olivecrona, 1953) and adrenalectomy (which is nearly always combined with ovariectomy) have been used as methods of treating cases of advanced cancer of the breast (Atkins, Falconer, Hayward, MacLean, and Schurr, 1966) and the results of comparative trials suggest that hypophysectomy is slightly the more effective of these two operations (Atkins, Falconer, Hayward, MacLean, Schurr, and Armitage, 1960). As an alternative to hypophysectomy neurosurgeons have sometimes use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
3

Year Published

1967
1967
1991
1991

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
1
13
0
3
Order By: Relevance
“…Surgical transection of the pituitary stalk results in growth of posterior lobe tissue at the proximal stump [9][10][11] and various degrees of infarction within the anterior lobe [12]. If …”
Section: Discussionmentioning
confidence: 99%
“…Surgical transection of the pituitary stalk results in growth of posterior lobe tissue at the proximal stump [9][10][11] and various degrees of infarction within the anterior lobe [12]. If …”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of the nerve fibers originates in the supraoptic and paraventricular nuclei of the hypothala mus. Anterior lobe dysfunction can also be explained by pituitary stalk transection which may cause infarc tion within the anterior lobe [12]. Because of docu mented perinatal trauma, Kikuchi et al [6] suggested that injury to the pituitary stalk had occurred at birth in most of their patients with neurohypophyseal ecto py.…”
Section: Discussionmentioning
confidence: 99%
“…But after mischotomy normally unimportant vessels raise their functional status. The artery of the trabecula, branch of the superior hypophyseal artery, plays then a definite pituitary feeding part (Nicolaidis, 1962;Adams et al, 1966). It is plausible then to suspect a physiological role misunderstood until now: indeed not only the ischaemia of the glandular parenchyma does not involve the areas in the immediate neighbourhood of the artery of the trabecula, but both the vascular and the cellular regenerations radiate from this vascular bed.…”
Section: Anatomical and Physiological Observationsmentioning
confidence: 99%
“…In side this large ischaemic area neocapillaries containing macrophages during the first days are in intimate contact with numerous indifferentiated cells which do not show orangeophile granules before the 17th day. Then there are two possibilities: (a) If the hypothalamo-pituitary interruption per sists the whole functional glandular parenchyma is made of these Azan oran geophile cells analogous to prolactin cells [1][2][3][4][5] . Furthermore it is now proved in human beings that the isolated pituitary produces the mammotrophic fac tor in excess 12 .…”
Section: Anatomical and Physiological Observationsmentioning
confidence: 99%